METODE TAZKIYAT AN-NAFS AL-GHAZALI DALAM PENDIDIKAN ISLAM UNTUK GENERASI MILENIAL - Dewi Aisyah; MuhammadZiyan Naufal; Syibromilisi Syibromilisi (Khulasah : Islamic Studies Journal, 2025)
This article was based on the problem of the need to improve spiritual quality by drawing closer to Allah through the tazkiyat al-nafs method. This is to cleanse the spirit of diseases that cause moral damage to humans. The aim of this paper is to produce output to analyze and explain the concept of tazkiyat an-nafs according to Al-Ghazali, in analyzing and explaining the phenomenon of moral crisis that occurs in the Millennial Generation, and explaining al-Ghazali's tazkiyat an-nafs method in overcoming the moral crisis in the Millennial Generation through several detections of the existence of aspects of monotheism, mukhafah, mahabbah, and ma'rifat. These four components must be possessed by someone who wants to meet their God (wushul ilallah) with various applications and stages that must be passed. The tazkiyat an-nafs process is an important method to be applied to the millennial generation in eliminating moral crises, which in general is also needed to make people have akhlakul karimah, pious character and noble behavior and have good quality of worship. If you succeed in carrying out all the tazkiyatun nafs processes properly, it will produce a person of physical and spiritual quality who is free from spiritual crises.